Micro-alloyed graphene / titanium alloy composite material and preparation method thereof
Patent Information
- Application Number
- CN202410143343.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-02-01
AI Technical Summary
[0006]本发明的目的是提供一种微合金化调控界面的石墨烯/TC4复合材料及其制备方法,以解决在制备综合性能更优异的石墨烯/Ti基复合材料过程中,石墨烯极易与钛发生严重的界面反应,导致制备的石墨烯/Ti基复合材料,强度提高程度较小,同时伴随塑性降低的问题
[0020] (1) The micro-alloyed graphene/TC4 composite material with controlled interface prepared by the present invention can significantly reduce the interfacial reaction between graphene and titanium by reasonable component ratio and ball milling and sintering settings, providing a new idea for the research of graphene-reinforced titanium-based composite materials.
Smart Images

Figure CN117904493B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphene / titanium-based composite materials technology, and in particular to a graphene / TC4 composite material with micro-alloying controlled interface and its preparation method. Background Technology
[0002] Titanium alloys are widely used in aerospace, defense, and automotive industries due to their excellent specific strength, corrosion resistance, high-temperature resistance, and good mechanical properties. After decades of development, the performance of titanium alloys has gradually approached its limits, and challenges remain in coping with increasingly demanding service conditions. To further improve the overall performance of titanium alloys, especially in extreme environments with high temperatures and high strain rates, and to achieve their wider applications, the composite use of titanium alloys has become an inevitable trend.
[0003] In recent years, carbon nanomaterials have demonstrated significant advantages in reinforcing metals due to their superior physical and mechanical properties. Commonly used carbon nanomaterial reinforcements include carbon nanotubes, nanodiamonds, and graphene. Graphene nanosheets, with their extremely large specific surface area, are considered to retain most of the excellent mechanical (ideally, graphene's tensile strength is approximately 130 GPa, and its Young's modulus is approximately 1.0 TPa), thermal, and electrical properties of graphene, and have shown outstanding reinforcing effects in polymer, ceramic, and metal matrices.
[0004] Compared to traditional titanium alloys reinforced with ceramic particles and whiskers, graphene / Ti composites exhibit superior strength, plasticity (toughness), and impact resistance, attracting widespread attention from researchers both domestically and internationally. However, due to the extremely high chemical reactivity of titanium, the problem of graphene readily undergoing severe interfacial reactions with it remains a significant challenge in the design and fabrication of graphene / Ti-based composites.
[0005] Currently prepared graphene / Ti-based composites show only a slight increase in strength compared to pure Ti, while exhibiting a decrease in plasticity. The most important reason for this is the easy formation of brittle interfacial reactants at the graphene-Ti matrix interface, which negatively impacts mechanical properties. Therefore, the most critical issue to be addressed is to suppress the reaction at the graphene-Ti matrix interface. Summary of the Invention
[0006] The purpose of this invention is to provide a graphene / TC4 composite material with micro-alloyed interface control and its preparation method, in order to solve the problem that graphene is prone to severe interfacial reaction with titanium during the preparation of graphene / Ti-based composite materials with better comprehensive performance, resulting in a small increase in strength and a decrease in plasticity of the prepared graphene / Ti-based composite material.
[0007] To achieve the above objectives, the present invention provides a graphene / TC4 composite material with microalloyed interface control and its preparation method. The graphene / TC4 composite material with microalloyed interface control is composed of the following components in mass percentage: graphene 0.80-1.00%, Al 6.20-6.40%, V 4.90-5.10%, Ta 0.75-0.95%, Mo 0.95-1.20%, Sn 1.10-1.30%, with the remainder being Ti and other unavoidable impurity elements.
[0008] Furthermore, it is composed of the following components by mass percentage: graphene 1.00%, Al 6.38%, V 5.06%, Ta 0.85%, Mo 1.01%, Sn 1.19%, with the remainder being Ti and other unavoidable impurity elements.
[0009] Furthermore, it is composed of the following components by mass percentage: 1.00% graphene, 6.40% Al, 5.10% V, 0.95% Ta, 1.20% Mo, 1.30% Sn, with the remainder being Ti and other unavoidable impurity elements.
[0010] Furthermore, it is composed of the following components by mass percentage: 0.80% graphene, 6.20% Al, 4.90% V, 0.75% Ta, 0.95% Mo, 1.10% Sn, with the remainder being Ti and other unavoidable impurity elements.
[0011] Furthermore, the microstructure of the graphene / TC4 composite material with microalloyed interface is as follows: density of 4.35-4.55 g / cm3 and compaction density of 99.34%.
[0012] A method for preparing a graphene / TC4 composite material with micro-alloyed interface control as described above, comprising the following steps:
[0013] S1. Ball milling: Add graphene, TC4 powder, and pure elemental powders of Ta, Mo, and Sn, along with grinding balls, into a ball mill jar. Place the ball mill jar on a ball mill, set the main disc speed to 300 rpm / min, and the ball milling time to 20 h. Use a ball milling mode of 20 min ball milling followed by 10 min intermittent milling. After ball milling, the composite powder is obtained.
[0014] S2. The obtained composite powder is subjected to plasma sintering. The sintering process parameters are set as follows: vacuum degree 5 Pa, heating rate 40-60℃ / min, sintering temperature 900-1000℃, axial pressure 40MPa, holding time 20min, and cooling rate 40-60℃ / min.
[0015] Furthermore, in step S1, the grinding jar is made of hardened chromium steel, and the grinding balls are made of ZrO2 material. The ratio of grinding balls with a diameter of 10mm to grinding balls with a diameter of 6mm is 3:4.
[0016] Furthermore, in step S1, the grinding jar needs to be cleaned with a brush and dried with water before loading the grinding balls and components, and then cleaned and dried with anhydrous ethanol; the ball-to-material mass ratio is 2:1; before placing the grinding jar on the ball mill, it is vacuumed three times in a vacuum environment.
[0017] Application of a graphene / TC4 composite material with a micro-alloyed interface as described above.
[0018] This invention modulates the graphene / Ti interface by adding different amounts of three alloying elements, Ta, Mo, and Sn. By changing the electronic distribution and interfacial bonding, the overall properties of the micro-alloyed graphene / TC4 composite material with a regulated interface are improved.
[0019] Therefore, the present invention provides a graphene / TC4 composite material with micro-alloyed interface control and its preparation method, the specific technical effects of which are as follows:
[0020] (1) The micro-alloyed graphene / TC4 composite material with controlled interface prepared by the present invention can significantly reduce the interfacial reaction between graphene and titanium by reasonable component ratio and ball milling and sintering settings, providing a new idea for the research of graphene-reinforced titanium-based composite materials.
[0021] (2) The microalloyed graphene / TC4 composite material with regulated interface prepared in this invention has a microhardness of 392 HV and a density of 4.48 g / cm³. 3 The density is 99.34%; compared with TC4 and graphene / TC4, the fracture strain is significantly improved, by 74.72% compared with TC4 and by 50.73% compared with graphene / TC4 composite material.
[0022] (3) The yield strength of the graphene / TC4 composite material with micro-alloyed interface prepared in this invention is 22.41% higher than that of TC4, and the compressive strength is 15.15% higher; compared with the graphene / TC4 composite material, the compressive strength is 7.44% higher.
[0023] (4) The preparation method of the graphene / TC4 composite material with micro-alloyed interface provided by the present invention is simple and easy to operate, has high preparation efficiency, saves energy, and is environmentally friendly in the preparation process, without generating any toxic or harmful substances, and can be used for industrial production.
[0024] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 The image shows a secondary electron image of the graphene / TC4 composite material with micro-alloying interface control in Example 1 of the present invention.
[0027] Figure 2 The image shows a SEM backscattered image of the graphene / TC4 composite material with micro-alloyed interface controlled in Example 1 of the present invention.
[0028] Figure 3 The images shown are bright-field images of the graphene / TC4 composite material with micro-alloyed interface control in Example 1 of the present invention, where (a) is a bright-field image, (b) is a high-resolution image of region 1, (c) is the electron diffraction pattern of region 1, (d) is a high-resolution image of region 2, and (e) is the electron diffraction pattern of region 2.
[0029] Figure 4 The TEM surface scan energy spectrum of the graphene / TC4 composite material with microalloyed interface control in Example 1 of the present invention is shown, where (a) is a bright field image, (b) is the elemental distribution map of Ti, (c) is the elemental distribution map of Al, (d) is the elemental distribution map of V, (e) is the elemental distribution map of C, (f) is the elemental distribution map of Mo, (g) is the elemental distribution map of Sn, and (h) is the elemental distribution map of Ta. Detailed Implementation
[0030] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0031] To make the objectives, technical solutions, and advantages of this application clearer, more thorough, and more complete, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments. The following detailed descriptions are all illustrations of embodiments, intended to provide further detailed explanation of the present invention. Unless otherwise specified, all technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0032] The materials and instruments used in the examples were all obtained commercially. TC4 was produced by Tianjin Fenghua New Material Technology Co., Ltd., with a particle size range of 100-200 μm.
[0033] Example 1
[0034] A graphene / TC4 composite material with micro-alloyed interface control was prepared by the following method:
[0035] S1. Clean the grinding jar made of hardened chromium steel and the grinding balls made of ZrO2 with clean water and a brush, let them air dry, then clean them three times with anhydrous ethanol, and then blow them dry. Each grinding jar contains 30 large grinding balls with a diameter of 10 mm and 40 small grinding balls with a diameter of 6 mm.
[0036] The chemical composition of the purchased TC4 was determined by X-ray diffraction analysis, and the results are shown in Table 1.
[0037] Table 1
[0038]
[0039] Based on the composition of TC4 shown in Table 1, the following raw materials were weighed using an analytical balance at a ball-to-material ratio of 2:1: 200g of ZrO2 grinding balls, 96.55g of commercial TC4 powder, 1.00g of graphene, 0.95g of Ta powder, 1.20g of Mo powder, and 1.30g of Sn powder. These were then sequentially poured into a ball mill jar. After three vacuum extractions under vacuum, the jar was placed on a ball mill. The main disc speed was set to 300 rpm / min, and the milling time was set to 20 hours. A 20-minute milling interval followed by a 10-minute interval was used for the mixed milling. The composite powder was obtained after the mixed milling was completed.
[0040] S2. The obtained composite powder was subjected to plasma sintering. The sintering process parameters were set as follows: vacuum degree 5 Pa, heating rate 50℃ / min, sintering temperature 1000℃, axial pressure 40 MPa, holding time 20 min, and cooling rate 50℃ / min. Cooling to ambient temperature yielded the microalloyed, interface-controlled graphene / TC4 composite material.
[0041] Example 2
[0042] A graphene / TC4 composite material with microalloyed interface control was prepared using the same method as in Example 1, except that the raw materials were accurately weighed using an analytical balance as follows: 200g of ZrO2 grinding ball, 95.95g of commercial TC4 powder, 1.00g of graphene, 0.85g of Ta powder, 1.01g of Mo powder, and 1.19g of Sn powder.
[0043] Example 3
[0044] A graphene / TC4 composite material with microalloyed interface control was prepared using the same method as in Example 1, except that the raw materials were accurately weighed using an analytical balance as follows: 200g of ZrO2 grinding ball, 96.40g of commercial TC4 powder, 0.80g of graphene, 0.75g of Ta powder, 0.95g of Mo powder, and 1.10g of Sn powder.
[0045] Example of effect 1
[0046] The microstructure of the graphene / TC4 composite material with microalloyed interface controlled by the microalloying obtained in Example 1 was observed using the following method:
[0047] A. The graphene / TC4 composite material with microalloyed interface obtained in Example 1 was wire-cut using wire cutting technology to obtain a sample block with a size of 5mm×5mm×5mm. The surface of the sample block was ground with 120#, 240# and 600# sandpaper in sequence until there were no obvious scratches on the surface. Then, it was polished carefully on a polishing machine. Water was continuously injected while the polishing machine was rotating until the surface of the sample block reached a scratch-free and bright state.
[0048] B. Immerse the sample block for 3 seconds using an etching solution composed of 7 mL H₂O + 1 mL HF + 2 mL HNO₃. Then observe the sample block using a scanning electron microscope (SEM). The SEM secondary electron image of the graphene / TC4 composite material with microalloyed interface regulation is shown below. Figure 1 As shown, the SEM backscattered image of the graphene / TC4 composite material with micro-alloyed interface is as follows: Figure 2 As shown.
[0049] Depend on Figure 1 and Figure 2 It can be seen that the graphene / TC4 composite material with micro-alloyed interface control is mainly composed of staggered lamellar α-structures distributed on the β-transformation matrix, and the generated second phase is distributed along the grain boundaries, forming an approximate network structure.
[0050] Example of effect 2
[0051] The mechanical properties of the graphene / TC4 composite material with micro-alloyed interface controlled by Example 1 were tested using the following methods:
[0052] Compression tests were performed on the microalloyed, interface-controlled graphene / TC4 composite material prepared in Example 1 using an electronic universal testing machine (MTS810 electronic universal testing machine). The sample size was Φ4×6mm, and the test temperatures were room temperature, 300℃, and 600℃. The maximum load of the equipment was 100KN, and the compression rate was 1mm / min.
[0053] The test results are shown in Table 2. The data for TC4 and graphene / TC4 materials are from the literature Preparation and properties of graphene-reinforced titanium alloy matrix composites with mesh structure [D] (Wang Juan, Southeast University, 2020).
[0054] Table 2
[0055]
[0056] As can be seen from Table 2, the graphene / TC4 composite material with micro-alloyed interface controlled by the present invention exhibits significant advantages in several aspects: First, compared with the traditional TC4 titanium alloy, the yield strength of the graphene / TC4 composite material with micro-alloyed interface controlled by the present invention is increased by 22.41%, and the compressive strength is also increased by 15.15%; Second, the fracture strain of the graphene / TC4 composite material with micro-alloyed interface controlled by the present invention is significantly improved, increasing by 74.72% compared with TC4.
[0057] The hardness of the graphene / TC4 composite material with microalloyed interface controlled by the microalloying control obtained in Example 1 was tested using a hardness tester (HV1000IS Vickers microhardness tester). The pressure value was 200g and the holding time was 6s. The results showed that the microhardness of the graphene / TC4 composite material with microalloyed interface controlled by the microalloying control obtained in Example 1 was 392HV.
[0058] After the graphene / TC4 composite material with microalloyed interface obtained in Example 1 was cleaned with sandpaper, it was ultrasonically cleaned, and then the surface of the composite material was dried. The density of the graphene / TC4 composite material with microalloyed interface was measured by the water displacement method, and the measurement was repeated 3 times.
[0059] The actual density calculation formula is: Where ρ S The actual measured density of the sample (g / cm³) 3 ), m1 is the mass of the sample in air (g), m2 is the mass of the sample in deionized water (g), ρ h The density of deionized water (g / cm³) 3 ).
[0060] The theoretical density is calculated based on the mixing principle, and the formula is: ρ l =∑ρ i V i , where ρ L The theoretical density (g / cm³) of the sample. 3 ), ρ i The theoretical density of the i-th phase (g / cm³) 3 V i Let be the volume fraction (vol%) of the i-th phase.
[0061] The formula for calculating density is: η is the density (%) of the sample.
[0062] The results showed that the density of the graphene / TC4 composite material with microalloyed interface controlled in Example 1 was 4.48 g / cm³. 3 The density is 99.34%.
[0063] Example of effect 3
[0064] A detailed microstructure analysis was performed on the graphene / TC4 composite material with microalloyed interface control prepared in Example 1, using the following methods:
[0065] The microalloyed graphene / TC4 composite material with a regulated interface prepared in Example 1 was cut into 0.4 mm thin slices using wire cutting. The samples were then polished to approximately 50 μm using 120# sandpaper. Finally, the samples were thinned using an ion thinner (GATAN695) to obtain samples suitable for transmission electron microscopy (TEM, Tecnai G2 F30, USA). Observation was performed using TEM and selected area electron diffraction. The results are as follows: Figure 3 and Figure 4 As shown, where Figure 3 (a) is a bright-field image, (b) is a high-resolution image of region 1; (c) is the electron diffraction pattern of region 1, (d) is a high-resolution image of region 2, and (e) is the electron diffraction pattern of region 2. Figure 4 (a) is a bright-field image, (b) is the Ti element distribution map, (c) is the Al element distribution map, (d) is the V element distribution map, (e) is the C element distribution map, (f) is the Mo element distribution map, (g) is the Sn element distribution map, and (h) is the Ta element distribution map.
[0066] Combination Figure 3 and Figure 4 As can be seen, the red area in the figure is rich in carbon, confirming it as graphene. At the same time, it is observed that Ta is abundant near the graphene, while Mo and Sn are less abundant and more uniformly distributed in this region.
[0067] Therefore, the microalloyed graphene / TC4 composite material with regulated interface prepared in this invention exhibits the most significant improvement in fracture strain compared to TC4 and graphene / TC4, increasing by 74.72% compared to TC4 and 50.73% compared to the graphene / TC4 composite material. The yield strength of the microalloyed graphene / TC4 composite material with regulated interface is 22.41% higher than that of TC4, and the compressive strength is 15.15% higher. Compared to the graphene / TC4 composite material, the compressive strength of the microalloyed graphene / TC4 composite material with regulated interface is 7.44% higher. This invention, through reasonable component ratios and ball milling and sintering settings, enables the prepared microalloyed graphene / TC4 composite material with regulated interface to achieve excellent comprehensive properties. The preparation method is simple, easy to operate, and environmentally friendly, generating no toxic or harmful substances.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A graphene / TC4 composite material with microalloyed interface control, characterized in that, It consists of the following components by mass percentage: graphene 0.80-1.00%, Al 6.20-6.40%, V 4.90-5.10%, Ta 0.75-0.95%, Mo 0.95-1.20%, Sn 1.10-1.30%, with the remainder being Ti and other unavoidable impurity elements; The preparation steps of the graphene / TC4 composite material with micro-alloyed interface are as follows: S1. Ball milling: Add graphene, TC4 powder, and pure elemental powders of Ta, Mo, and Sn, along with grinding balls, into a ball mill jar. Place the ball mill jar on a ball mill, set the main disc speed to 300 rpm / min, and the ball milling time to 20 h. Use a ball milling mode of 20 min ball milling followed by 10 min intermittent milling. After ball milling, the composite powder is obtained. S2. The obtained composite powder is subjected to plasma sintering. The sintering process parameters are set as follows: vacuum degree 5 Pa, heating rate 40-60℃ / min, sintering temperature 900-1000℃, axial pressure 40MPa, holding time 20min, and cooling rate 40-60℃ / min.
2. The graphene / TC4 composite material with microalloyed interface control according to claim 1, characterized in that, It consists of the following components by mass percentage: graphene 1.00%, Al 6.38%, V 5.06%, Ta 0.85%, Mo 1.01%, Sn 1.19%, with the remainder being Ti and other unavoidable impurity elements.
3. The graphene / TC4 composite material with microalloyed interface control according to claim 1, characterized in that, It consists of the following components by mass percentage: graphene 1.00%, Al 6.40%, V 5.10%, Ta 0.95%, Mo 1.20%, Sn 1.30%, with the remainder being Ti and other unavoidable impurity elements.
4. The graphene / TC4 composite material with micro-alloyed interface control according to claim 1, characterized in that, It consists of the following components by mass percentage: graphene 0.80%, Al 6.20%, V 4.90%, Ta 0.75%, Mo 0.95%, Sn 1.10%, with the remainder being Ti and other unavoidable impurity elements.
5. The graphene / TC4 composite material with microalloyed interface control according to claim 1, characterized in that: The microstructure of the graphene-reinforced TC4 composite material with microalloyed interface control is characterized by a density of 4.35-4.55 g / cm³. 3 The density is 99.34%.
6. The graphene / TC4 composite material with microalloyed interface control according to claim 1, characterized in that: In step S1, the grinding jar is made of hardened chromium steel and the grinding balls are made of ZrO2 material. The ratio of grinding balls with a diameter of 10mm to grinding balls with a diameter of 6mm is 3:
4.
7. The graphene / TC4 composite material with microalloyed interface control according to claim 1, characterized in that: In step S1, the grinding jar needs to be cleaned with a brush and dried with water before loading the grinding balls and components. Then it needs to be cleaned and dried with anhydrous ethanol. The mass ratio of grinding balls to materials is 2:
1. Before placing the grinding jar on the ball mill, it needs to be vacuumed three times in a vacuum environment.
Citation Information
Patent Citations
Graphene reinforced titanium-based composite material characterized by three-dimensional network-shaped distribution, preparation method thereof and application thereof
CN109022907A